Mechanical and Structural Responses of Low Carbon Steel to Cold Rolling and Stress Relief Anneal Treatments - Bodude, M. A.; Ayoola, W. A.; Oyetunji, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This study investigated the effect of deformation by cold rolling and stress relief anneal on the mechanical and structural properties of low carbon steel. The as-received steel samples were cold rolled at 20% – 40 % degrees of deformation using Buhler rolling machine in Metallurgical and Materials engineering department University of Lagos, Nigeria. Additionally, some of the cold rolled samples were annealed at a temperature of 650° C and soaked for 1 hour in a muffle furnace. The results revealed that the ultimate tensile strength (UTS), percent elongation, hardness and impact strength of the cold rolled low carbon steel improved significantly after stress relief anneal due to the elimination of induced strain hardening caused by cold rolling. The micrographs show that cold rolled + stress relief anneal caused significant recrystallization of ferrite-austenite phase to refine martensite with reduction of dislocations. Therefore, the low carbon steel can be used effectively for structural purposes in machines and equipment.